Long Term Weight Loss Diets and Obesity Indices: Results of a Network Meta-Analysis - Jabbour, Jana; Rihawi, Yasmin; Khamis, Assem M.; Ghamlouche, Layal; Tabban, Bayan; Safadi, Gloria; Hammad, Nour; Hadla, Ruba; Zeidan, Marwa; Andari, Dana; Azar, Riwa Nour; Nasser, Nadine; et al. (Frontiers in Nutrition, 2022)
Background: Scientists have been investigating efficient interventions to prevent and manage obesity. This network meta-analysis (NMA) compared the effect of different diets [moderate macronutrients (MM), low fat/high carbohydrate (LFHC), high fat/low carbohydrate/ (HFLC) and usual diet (UD)] on weight, body mass index (BMI) and waist circumference (WC) changes at ≥12 months. Methods: We searched Medline, Embase, PubMed databases and the Cochrane Library. We systematically assessed randomized controlled trials (RCTs) evaluating dietary interventions on adults (mean BMI ≥25 kg/m2) receiving active dietary counseling for ≥12 months. We pooled the data using a random-effect NMA. We assessed the quality of the included RCTs using the Cochrane risk of bias tool. Results: We included 36 trials, 14 of which compared HFLC to MM diets. Compared to UD, all diets were associated with a significant weight loss (WL) at ≥12 months, HFLC [Mean Difference in kg (95% CI): -5.5 (-7.6;-3.4)], LFHC [-5.0 (-7.1;-2.9)] and MM [-4.7 (-6.8;-2.7)]. HFLC, compared to MM diet, was associated with a slightly higher WL (of -0.77 kg) and drop in BMI (of -0.36 kg/m2), , while no significant difference was detected in other dietary comparisons. There was no significant interaction of the results with the pre-specified sub-groups. The risk of bias was ‘High’ in the majority of the studies, mostly related to incomplete data reporting, lack of blinding of participants, providers and outcome assessors. Conclusion: Dietary interventions extending over ≥12 months are superior to UD in inducing weight, BMI and WC loss. HFLC might be associated with a slightly higher WL compared to MM diets.